The Influence of the Grid Structure on the Function of Architectural Space - Andi Asrul Sani (Indonesian Journal of Built Environmental and Sustainability, 2020)
Some researchers use the theory of utilization, capacity and occupancy to measure room use. Space capacity needs to be determined in the planning of building space, because it gives a big impact on fixed costs, especially building rooms that provide economic value. Planning a room's capacity also determines whether the demand for space can be met, or whether the existing space will be excessive (Martinich, 1997). Architectural works, which appeared as a container to accommodate human activities. Often the arrangement of spatial functions in one building is still not optimally integrated, so that there are one or more functions that are less effective (may be too narrow so uncomfortable to use or may be too broad to cause waste). All functions in the space need to be analyzed functionally so as to get maximum effectiveness in the division of space that is integrated with the column column structure modul. This study will discuss the effectiveness of the division of space in building design as an effort to integrate the system of spatial division with the amount of grid column structure.The research method was carried out qualitatively with a case study approach, and took the location of lecture rooms at the Institut Teknologi Sumatera (ITERA). The study was conducted aimed at knowing how the effect of the determination of the grid structure on space in this case focuses on the function of the lecture room. Broadly speaking, it can be concluded that the selection of the right structural grid can affect the effectiveness and efficiency of space both related to the comfort of the user space and the capacity of the lecture room. Therefore the most effective and efficient grid structure related to lecture space according to the case study above is 6000 mm x 7500 mm with a maximum capacity of 30 people for small classes while large classes can accommodate a maximum of 66 people or standard space requirements of 1.2 m2 / students with 20% flow. The grid structure is also in accordance with the modular system in SNI 03-1978-1990 which is a multiple of 30 cm.